Lithuanian women's judo championship matches (time-motion) peculiarities - Dudeniene, L.; Skarbalius, A. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
Our hypothesis (light weight matches time-motion data significantly vary with heavy weight categories) proved only partially, since it was found significant differences only between 52 kg and 70 kg weight categories. However, the obvious differences between the lightest and heaviest categories - the heaviest weight category (over 78 kg) athletes in almost all time-motion (except groundwork combat time) indicators are maximum.